The Role of Student Teams Achievement Divisions (STAD) in Improving Student’s Learning Outcomes - Yuliani, Nina (Unversitas Negeri Malang, 2019)
This study addressed to cope the students problems in the classroom by implementing cooperative learning methods with the Students Team Achievement Division (STAD) technique. The study followed a classroom action research through four stages namely planning, implementing, observing, and reflecting action. This research subjected to SMA Negeri 7 Malang in Indonesia in economics subject. This research was conducted in two cycles consisting of two meetings for each. The data were gathered using observation, tests, and documentation. The results of the study showed the implementation of the Students Team Achievement Division (STAD) learning technique on economic subjects showed that it could improve students’ learning outcomes from the cognitive domain. The increasing of cognitive learning outcomes is indicated by an enhancement in the average value and the percentage of mastery learning in classical. Furthermore, the application of this technique can also increase the role, enthusiasm, and cooperation between students in heterogeneous groups.Keywords: STAD, learning outcomes, cooperative learning